2020
DOI: 10.5194/isprs-archives-xliv-4-w3-2020-71-2020
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of 3d Point Cloud Triangulation for Smart City Modelling and Visualization

Abstract: Abstract. The current trends of 3D scanning technologies allow us to acquire accurate 3D data of large-scale environment efficiently. The 3D data of large-scale environments is essential when generating 3D model is for the visualization of smart cities. For the seamless visualization of 3D model, large data size will be used during the 3D data acquisition. However, the processing time for large data size is time consuming and requires suitable hardware specification. In this study, different hardware capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Li et al, 2021) settings such as assets (S. Y. Lee et al, 2013), sites area (Shih & Wang, 2014), cities (Buyuksalih et al, 2019;Park &Guldmann, 2019), andvegetation (Mesas-Carrascosa et al, 2020;Yang et al, 2015); the obtained 3D point clouds represent an important type of geospatial data that categorized and utilised in wide range of geoinformation applications and systems (Ariff et al, 2020;Discher et al, 2018;Richter et al, 2015). Ariff et al, (2020) experimented 3D model meshing of 2.77 GB Putrajaya city using two different GPU, NVIDIA GEOFORCE GTX 1070 and NVIDIA GEOFORCE GTX 850M and they concluded that a graphic card with a higher graphic and computing performance is essential for smoother and faster visualization of 3D model and shorter time processing and lesser technical issue.…”
Section: Smart Citiesmentioning
confidence: 99%
“…Li et al, 2021) settings such as assets (S. Y. Lee et al, 2013), sites area (Shih & Wang, 2014), cities (Buyuksalih et al, 2019;Park &Guldmann, 2019), andvegetation (Mesas-Carrascosa et al, 2020;Yang et al, 2015); the obtained 3D point clouds represent an important type of geospatial data that categorized and utilised in wide range of geoinformation applications and systems (Ariff et al, 2020;Discher et al, 2018;Richter et al, 2015). Ariff et al, (2020) experimented 3D model meshing of 2.77 GB Putrajaya city using two different GPU, NVIDIA GEOFORCE GTX 1070 and NVIDIA GEOFORCE GTX 850M and they concluded that a graphic card with a higher graphic and computing performance is essential for smoother and faster visualization of 3D model and shorter time processing and lesser technical issue.…”
Section: Smart Citiesmentioning
confidence: 99%